Building a future group by group: case studies on self help groups in India - Srinivasan, Girija (ed.) (Lucknow)
Micro credit in India has come of age. It is no longer relegated to the confines of specialised and relatively obscure corners of donor agencies and NGOs. There are numerous variants of micro credit which are in vogue in India. Though the technologies of different micro-credit programmes may be different, the basic premise on which they work is to take financial services to the poorer sections of the people who have been hitherto neglected by the formal financial system as being unbankable. Among the variants of micro-credit programmes in India, the Self Help Group (SHG) linkage programme has been showing signs of faster progress as well as high rate of success. The initiative for this programme has been taken by the National Bank for Agriculture and Rural Development (NABARD) which sponsored an Action Research Project in 1986-87. Through this project grew the Pilot Project which was formalised by Reserve Bank of India and NABARD in 1992. The pilot project initiated by NABARD pioneered an attempt to bring together the main-stream banking system and the rural poor through SHGs. The SHG linkage programme attempts to bring together four trends and derives strength from the positive environment created by these independently of each other.
Keywords: Rural development-India